(3JMaI GdadGM deG dg ajg ef GdUdGMs - (3SYjO Hf eMeO GdeGLQjs
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdaQO SHMGfg ef eSJMb GdMeO eHJOY GdCadGc hGdCQVjfG hLGA Ydi GdTghQ hGdSfjfG SejJg HJMaI GdadGM deGdg ajg ef GdUdGM s
(3BNQgG (B:s
(3hajg jJbi MeC GdeSGLf hJLeY GdejGg ai GdeNGRf hgGgfG aQZJ ef PG GdQLR ajeG bUOJ HcdGe ehLR Je HMeO Gddg s
(3CQLhRI ai Ydhe GdJfLjes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B255 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeY GdTjN EHQGgje HGTG (B- (3GdCScfOQjI (B(33) s
Keywords: (3Gdadcs